Spontaneously Ruptured Gastrointestinal Stromal Tumor With Pelvic Abscess: A Case Report and Review - Ulusan, Serife (Gastroenterology Res, 2009)
Gastrointestinal stromal tumors (GISTs) originate from interstitial Cajal cells on intestinal pacemaker cells that arise from the muscularis propria of the gastrointestinal tract wall. GISTs are characterized by the expression of c-KIT protein (CD 117, stem cell factor receptor) and are the most common mesenchymal tumors of the digestive tract. That protein, which is detected via immunohistochemical analysis, is the primary diagnostic criterion for a GIST. The rupture of a gastrointestinal stromal tumor of the peritoneal cavity is critical complication, although it is infrequently described in the literature. We describe the computed tomographic findings of a ruptured gastrointestinal stromal tumor of the jejunal wall with an accompanying abscess. We also review the clinical features, radiologic and pathologic findings, and treatment of similar previously reported cases.